A rare presentation of primary cutaneous basaloid squamous cell carcinoma of scalp - Javid, Mohamed; Swaminathan, Shanthi Ponnandai; Jebasingh, Arun Victor; Velayutham, Manivannan; Kawarat, Vikas (International Surgery Journal, 2018)
Basaloid squamous cell carcinoma (BSSC) is a rare and aggressive variant of squamous cell carcinoma (SCC). It has predilection for the upper aero digestive tract with common metastasis to regional lymph node and common distant metastasis to lungs. While metastasis to scalp has rarely been reported, primary occurrence of BSCC arising from scalp has hardly ever been reported. We are reporting a case of 70 year female patient, who presented with an ulceroproliferative growth in posterior scalp. Biopsy from the edge of growth was reported as malignant adnexal tumor. A wide local excision was done and that biopsy was reported as Basaloid squamous cell carcinoma. We intend to present this case, considering its rarity and its primary presentation in an very unusual and unique location for this variant.